Rice Weevil as a Storage Pest - Yeasmin, Shahina (Journal of Discoveries in Applied and Natural Science, 2026)
The observation of food preferences of the rice weevil, Sitophilus oryzae, reveals that it exhibits a strong preference for polished rice, with studies showing that it prefers polished rice over other grains when conditions favor infestation. The damage in polished rice was measured at approximately 20%, indicating its high preference for this grain. In contrast, oats showed higher resistance against rice weevil, with minimal damage and weight loss. This suggests that the presence of natural defence compounds in oats, such as avenacosides, phenolics, and fatty acids, contributes to their resistance against storage pests.